PENGARUH KERJASAMA ORANG TUA DAN GURU TERHADAP DISIPLIN PESERTA DIDIK DI SEKOLAH MENENGAH PERTAMA (SMP) NEGERI KECAMATAN JAGAKARSA - JAKARTA SELATAN - Hidayat, Syarif (Jurnal Ilmiah Widya, 2013)
The collaboration between parents and the school teacher is very important in education process in order to achieve the goal. The objective of this research is to find out the effect of parent collaboration with the teacher on student discipline. The research was conducted at junior high school at South Jakarta on September till October 2012. The research used survey method and correlation analysis techniques with samples 250 selected proportionally and questionnaire with Likert Scale model. The research findings are: (1) the parent collaboration with the teacher still on the low level especially communication and parent participation to the role of school is established, (2) there is an effect of parent collaboration with the teacher on the student discipline,(3) the student discipline is effected by the variation of parent collaboration with the teacher.